Reliability of Five Rapid D-Dimer Assays Compared to ELISA in the Exclusion of Deep Venous Thrombosis - Janssen, M C H; Heebels, A E; de Metz, M; Verbruggen, H; Wollersheim, H; Janssen, S; Schuurmans, M M J; Nováková, I R O (Thrombosis and Haemostasis, 1997)
Studies measuring the fibrin degradation product D-Dimer (DD) using enzyme-linked immunosorbent assays (ELISA) in patients with venographically proven deep venous thrombosis (DVT) suggest that it is possible to exclude DVT when DD level is below a certain cut-off level. However, ELISA methods are time-consuming and not available in all laboratories. Different rapid latex-agglutination assays have been investigated, but their sensitivity is considerably lower.In the present study we compared the value of four novel latex DD tests (Tinaquant®, Minutex®, Ortho® and SimpliRed®) and one rapid ELISA (VIDAS®) to a classical ELISA DD assay (Organon Mab Y18®) in 132 patients suspected of DVT.The VIDAS®, a new quantitative automated ELISA, had a sensitivity of 100% and a negative predictive value of 100% for both proximal and distal DVT at a cut-off level of 500 ng/ml. The Tinaquant® assay, a new quantitative latex method, had a sensitivity of 99% and a negative predictive value of 93% for both proximal and distal DVT at a cut-off level of 500 ng/ml. For proximal DVT only, both assays had a sensitivity and negative predictive value of 100%. VIDAS® and Tinaquant® correlated well with ELISA (correlation of r = 0.96 and r = 0.98 respectively). Sensitivities of the semi-quantitative latex assays Minutex®, Ortho® and SimpliRed® were considerably lower (77%, 51 % and 61 % respectively).These results suggest that VIDAS® and Tinaquant® may be used instead of ELISA DD in the exclusion of DVT. Tinaquant® can be performed within 20 min and VIDAS® within 35 min. Both assays might be used as a routine screening test and should be evaluated in large clinical management studies.